2016
DOI: 10.3390/children3040033
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Rehabilitation Programs for Children and Adolescents with Severe Disabling Chronic Pain: Indications, Treatment and Outcomes

Abstract: Children and adolescents with highly disabling chronic pain of high intensity and frequency are admitted to specialized pain rehabilitation programs. Some barriers to obtaining this specialized care include a lack of availability of treatment centers, a perceived social stigma and individual barriers such as socioeconomic status. Specialized rehabilitation programs for severe disabling chronic pain worldwide have similarities regarding admission criteria, structure and therapeutic orientation. They differ, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 58 publications
(231 reference statements)
3
54
0
1
Order By: Relevance
“…Our findings were consistent with those of previous studies, which demonstrated that children who were highly affected by chronic pain improved in response to inpatient treatment in regard to functional impairment, pain intensity and quality of life [ 4 , 11 , 37 , 38 ]. Although there exists strong evidence for the short-term effectiveness of inpatient treatment, research concerning the long-term outcome is rare, and tools for measuring treatment outcomes need to be standardized for better comparability [ 38 ]. A meta-analysis by Hechler and colleagues demonstrated that intensive interdisciplinary pain treatment has positive treatment effects on pain intensity, disability and depressive symptoms, though school functioning and anxiety were excluded due to the heterogeneity in the treatment outcome measures [ 4 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were consistent with those of previous studies, which demonstrated that children who were highly affected by chronic pain improved in response to inpatient treatment in regard to functional impairment, pain intensity and quality of life [ 4 , 11 , 37 , 38 ]. Although there exists strong evidence for the short-term effectiveness of inpatient treatment, research concerning the long-term outcome is rare, and tools for measuring treatment outcomes need to be standardized for better comparability [ 38 ]. A meta-analysis by Hechler and colleagues demonstrated that intensive interdisciplinary pain treatment has positive treatment effects on pain intensity, disability and depressive symptoms, though school functioning and anxiety were excluded due to the heterogeneity in the treatment outcome measures [ 4 ].…”
Section: Discussionsupporting
confidence: 93%
“…The presence of limited resources available in communities to manage children with chronic pain has been shown to be a significant barrier in several countries [1921]. There are only two pediatric pain comprehensive programs in the Los Angeles County (population 2,325,047 according to the 2015 census) [22] which can explain the delay to access our services: the average waiting time for an evaluation at our clinic is 7 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the core aspects of the development and maintenance of chronic and recurrent pain are dysfunctional, passive coping strategies, such as inactivity and social withdrawal (Simons and Kaczynski, ). In clinical populations, pain education is an important part of chronic pain treatment (Stahlschmidt et al., ). Students who have not yet developed a severe chronic pain disorder may also benefit from education to prevent dysfunctional coping and pain chronification.…”
Section: Introductionmentioning
confidence: 99%